Tetramethylpyrazine Protects against Early Brain Injury after Experimental Subarachnoid Hemorrhage by Affecting Mitochondrial-Dependent Caspase-3 Apoptotic Pathway. (27th February 2017) - Li, Shaoxue; Xiao, Xiaolan; Ni, Xiaojia; Ye, Zhennan; Zhao, Junjie; Hang, Chunhua
Abstract : This study was to test the hypothesis that tetramethylpyrazine (TMP) protected against early brain injury after subarachnoid hemorrhage (SAH) by affecting the mitochondrial-dependent caspase-3 apoptotic pathway. TMP was administrated after the rats' prechiasmatic SAH mode. Animal neurobehavioral functions were assessed and the mitochondrial morphology, mitochondrial and cytoplasmic calcium, and mitochondrial membrane potential changes (Δ ψ m) of the brain tissues were measured. The expressions of cytoplasmic cytochrome c (cyt c), second mitochondria-derived activator of caspases (Smac), and cleaved caspase-3 B-cell lymphoma 2 (bcl-2) in cells were determined and cellular apoptosis was detected. The treatment of TMP resulted in less apoptotic cells and milder mitochondrial injury and potentially performed better in the neurobehavioral outcome compared to those with saline. Also, TMP ameliorated calcium overload in mitochondria and cytoplasm and alleviated the decrease of Δ ψ m. In addition, TMP inhibited the expression of cytoplasmic cyt c, Smac, and cleaved caspase-3, yet it upregulated the expression of bcl-2. These findings suggest that TMP exerts an antiapoptosis property in the SAH rat model and this is probably mediated by the caspase-3 apoptotic pathway triggered by mitochondrial calcium overload. The finding offers a new therapeutic candidate for early brain injury after SAH.